Striking a Balance: Exploring Harmony in Indonesian Criminal Law and Islamic Jurisprudence - Royani, Yayan Muhammad; Park, Hee Cheol (Universitas Islam Negeri Walisongo Semarang, 2023)
The long-established the Indonesian Criminal Code follows a liberal individual's tradition of Dutch criminal law that has always changed. The old criminal code is based on classical and neo-classical thinking, emphasising systematic criminal law structures and legal certainty. The basis of balance in the new criminal code is a response to a base that does not reflect the nation's values. For example, Pancasila is included as a foundation, including the value of the most exquisite element of divinity in its formulation. With the value of divinity, it is necessary to review from the perspective of religious teachings, including Islam. Islamic criminal law reflects the spirit of balance in the criminal provisions of hudud, qisas, and takzir. This article uses a comparative approach and a type of normative research. The results of the article show that the relevance of the primary balance in the new criminal code and Islamic Criminal Law is seen in several aspects, such as the relevancy of the pillar values of the balance in Pancasila, the relevancy of the fundamental balance of the mono-dualistic; the significance of the idea of a balance between the protection of victims and the individualization of criminals; and the fundamental relevance to the balance between formal and material criteria.Hukum pidana Indonesia yang sudah lama digunakan mengikuti tradisi individu bebas dari hukum pidana Belanda yang selalu berubah. Hukum Pidana lama didasarkan pada pemikiran klasik dan neo-klasik, menekankan struktur hukum pidana yang sistematis dan kepastian hukum. Dasar keseimbangan dalam Hukum Pidana baru adalah respons terhadap basis yang tidak mencerminkan nilai-nilai bangsa. Misalnya, Pancasila dimasukkan sebagai fondasi, termasuk nilai unsur ilahi yang paling indah dalam formulasinya. Dengan nilai ilahi, perlu untuk meninjau dari perspektif ajaran-ajaran agama, termasuk Islam. Hukum pidana Islam mencerminkan semangat keseimbangan dalam ketentuan pidana hudud, qisas, dan takzir. Artikel ini menggunakan pendekatan komparatif dan jenis penelitian normatif. Hasil penelitian menunjukkan bahwa relevansi keseimbangan primer dalam kode kriminal baru dan hukum pidana Islam terlihat dalam beberapa aspek, seperti relevansi nilai-nilai pilar keseimbangannya di Pancasila, relevansi ekuilibrasi fundamental mono-dualistik; pentingnya gagasan kestabilan antara perlindungan korban dan individualisasi penjahat; dan relevansi fundamental untuk kesequilibrasi kriteria formil dan materiil.